A Comprehensive Approach to Assessment of Testamentary Capacity - Kenepp, Amanda; Johnson, Ellen; Lee, Grace J.; Sunderaraman, Preeti; Denburg, Natalie L.; Nguyen, Christopher M. (Frontiers in Psychology, 2021)
The growing aging population raises important implications for legal and clinical systems, including testamentary capacity (TC) assessment. Yet, there are limited comprehensive and standardized assessment measures for TC readily available for clinical use. A review of current assessment methods and standardized approaches for TC assessment is provided. Although several guidelines regarding TC assessment have been proposed in prior literature, existing standardized approaches do not appear to meet full criteria for TC. A comprehensive approach to assessment of testamentary capacity is proposed.